Getting under the Skin: Report from the International Psoriasis Council Workshop on the Role of Stress in Psoriasis - Schwartz, Julia; Evers, Andrea W. M.; Bundy, Christine; Kimball, Alexandra B. (Frontiers in Psychology, 2016)
Psoriasis is a chronic inflammatory skin condition with significant physical and psychosocial comorbidity. A workshop of leading experts in dermatology and psychology with the purpose of better understanding the current role of psychological comorbidities in psoriasis was held by the International Psoriasis Council in November 2013. The role of stress reactivity with a focus on the hypothalamic-pituitary-adrenal axis was emphasized. While cognitive behavioral therapy remains the most extensively studied and successful treatment strategy in patients with psoriasis and various psychological comorbidities, new and innovative interventions such as online-based therapies have recently emerged. Strategies and recommendations towards approaching psychological comorbidities are discussed.